2006
DOI: 10.1128/aem.72.1.784-792.2006
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Rat Cecal Microbiota by Administration of Raffinose and Encapsulated Bifidobacterium breve

Abstract: To investigate the effects of administration of raffinose and encapsulated Bifidobacterium breve JCM 1192 T cells on the rat cecal microbiota, in a preclinical synbiotic study groups of male WKAH/Hkm Slc rats were fed for 3 weeks with four different test diets: basal diet (group BD), basal diet supplemented with raffinose (group RAF), basal diet supplemented with encapsulated B. breve (group CB), and basal diet supplemented with both raffinose and encapsulated B. breve (group RCB). The bacterial populations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 47 publications
2
65
2
1
Order By: Relevance
“…1), corroborated by the comparative genome analysis presented below (see Fig. 2), and on other reports in the literature regarding raffinose utilization by bifidobacteria, raffinose-type sugar utilization appears to be an ubiquitous property of bifidobacteria, supporting previous publications on the prebiotic potential of (some of) these sugars (65)(66)(67)(68). Although transcription of the raf gene cluster of B. breve is induced in the presence of either raffinose, melibiose, or stachyose, it has been shown that the raffinose system in Streptococcus pneumoniae is upregulated in the presence of raffinose but not melibiose, suggesting differential regulatory mechanisms (69).…”
Section: Resultssupporting
confidence: 73%
“…1), corroborated by the comparative genome analysis presented below (see Fig. 2), and on other reports in the literature regarding raffinose utilization by bifidobacteria, raffinose-type sugar utilization appears to be an ubiquitous property of bifidobacteria, supporting previous publications on the prebiotic potential of (some of) these sugars (65)(66)(67)(68). Although transcription of the raf gene cluster of B. breve is induced in the presence of either raffinose, melibiose, or stachyose, it has been shown that the raffinose system in Streptococcus pneumoniae is upregulated in the presence of raffinose but not melibiose, suggesting differential regulatory mechanisms (69).…”
Section: Resultssupporting
confidence: 73%
“…Non-digestible food ingredients that promote the growth and/or activity of probiotics are termed prebiotics. Several oligosaccharides, such as raffinose, 2,3) fructo-oligosaccharide, 4,5) and galacto-oligosaccharide, [6][7][8] are known to function as prebiotics for bifidobacteria, and thus are specifically termed bifidus (or bifidogenic) factors.…”
mentioning
confidence: 99%
“…Based on the log phase of growth patterns, it can be seen specific growth rate (μ) of isolate bacteria KE-B6 that is equal to 0377 / hr and a generation (g) of 1.84 hours. This value is very important to predict the amount of biomass and the product to be produced (Waites et al, 2001;Madigan, 2009;Dinoto et al, 2006;Dinoto et al, 2013). Phase lag or adjustment phase of the cell with the environment (medium) does not occur in the growth of isolate bacteria KE-B6, is due to the adjustment phase have been occured when the starter in the fermentation for 22 hours on a rotary shaker before being mixed in media production.…”
Section: The Growth Of Isolate Bacteria Ke-b6mentioning
confidence: 99%
“…Culture production medium is then taken 1.5 ml for centrifuged at 3000 rpm for 10 minutes. At this stage it was also determined specific growth rate and generation time (Waites et al, 2001, Dinoto et al, 2006Dinoto et al, 2013).…”
Section: Introductionmentioning
confidence: 99%